Análisis de riesgo del sistema de captación del acueducto de Ibagué-Tolima, por procesos erosivos en la cuenca del Río Combeima (2019)
Erosion understood as soil degradation is a process that modifies the geometry of slopes facilitating the occurrence of mass removal processes and whose deposition of disaggregated particles to water bodies translates into pollution. In the same way, it has been found that changes in land use and inadequate management of it affect the loss of soil and sediment production in a basin level are deposited in the river. Therefore, this work proposes as a general objective to develop a methodological proposal for the evaluation of the physical risk of the Ibagué - Tolima aqueduct collection system by erosive processes from the Combeima River basin, considering different conditions of land use. For this purpose, the TETIS hydrological model was applied as well as its sediment submodel in addition to the HEC-RAS hydraulic model. Among the results obtained, the identification of sediments produced in the basin are highlighted, as well as the description of the magnitude of flood events and floods related to land uses such as pastures, crops and forests.